DAMPAK KUALITAS PRODUK, CITRA MEREK, DAN HARGA TERHADAP LOYALITAS KONSUMEN MELALUI KEPUASAN: (Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Dian Nuswantoro Pengguna Laptop Acer) - Rudianto, Muhammad; Farida, Ida; Anomsari, Ariati; Purusa, Nanda Adhi (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
This study examines the effect of product quality, brand image, and price on consumer loyalty through satisfaction in students using Acer laptops at Dian Nuswantoro University. Data were collected from 115 respondents and analyzed using PLS-SEM through SmartPLS 4.0 software. The results show that product quality and brand image have a positive and significant effect on satisfaction, while price does not have a significant effect on satisfaction. On the other hand, only brand image and consumer satisfaction are proven to have a significant effect on consumer loyalty, while product quality and price do not show a significant direct effect on loyalty. However, product quality is proven to have an indirect effect on consumer loyalty through consumer satisfaction as a mediating variable. These findings emphasize the importance of improving quality and brand image to build loyalty.